Application of Ecological Theological Reflection Based on the Biblical Passage Col 1:15-20 - Nhat , Vo Dinh (Asian Journal of Philosophy and Religion, 2025)
This study examines Colossians 1:15–20 to This study examines Colossians 1:15–20 to articulate a Christocentric theology of creation and reconciliation in response to the ecological crisis. Employing exegetical analysis, the research identifies Jesus Christ as the cosmic center and fullness of God, integral to both creation and the restoration of peace. This research suggests that ecological conversion must be grounded in a theology that recognizes nature as part of God’s salvific mission. Drawing inspiration from Pope Francis’s Encyclical Letter Laudato Sí, the study proposes a holistic ecological education model based on eco-spirituality and practical initiatives such as the RBE model (Renewable energy, Biodiversity, and Education). This model fosters environmental stewardship, promoting justice, solidarity, and sustainable living. This paper concludes that missionary-oriented ecological education can cultivate a transformative relationship with creation and restore harmony between humanity and the environment.